Organizational Work, Well-Being, and Quality of Life at an Elderly Age: The Case of Cyprus - George Papageorgiou; Panagiota Athanasiadou; Elena Tsappi; Sofia A. Xergia; Athanasios Maimaris; Andreas Efstathiades (Journal of Aging Research)
This study investigates the impact of postretirement organizational work on the well-being and overall quality of life of the elderly population in Cyprus. Specifically, it evaluates the multifaceted effects of continued employment after retirement, based on data collected through a survey administered to a representative sample of elderly Cypriots. The research findings, informed by prominent instruments in the field, demonstrate significant enhancements in autonomy, self-actualization, and both physical and psychological well-being for the elderly as a result of continuing to work beyond retirement age. Through inferential statistical analysis, the study identifies several key factors contributing to significant improvements in people’s lives. Particularly, the findings reveal a positive correlation between sustained employment and several aspects of quality of life, challenging conventional views on retirement. These insights hold particular relevance for the Cypriot context and suggest broader implications for policymaking that encourage postretirement employment as a means to enhance well-being in countries with aging populations. Overall, this paper contributes to the discourse on organizational work, aging, and quality of life by offering evidence-based policy recommendations for enhancing human self-actualization and well-being through sustainable professional engagement.